Galkinius nom.nov., replacement name for Galkinia Ross & Newman, 1995 - Perreault, Ray T. (Zootaxa, 2014)
In 1995, Ross & Newman proposed Galkinia as a replacement name for Utinomia Galkin, 1986 (Cirripedia: Pyrgomatidae), which was pre-occupied. However, this author discovered Galkinia was itself pre-occupied by a genus of fossil fish, Galkinia Ghekker, 1948 (Actinopterygii: Pholidophoriformes).